2019
DOI: 10.1177/2325967119886591
|View full text |Cite
|
Sign up to set email alerts
|

Health State Utilities in Children and Adolescents With Osteochondritis Dissecans of the Knee

Abstract: Background: The impact of osteochondritis dissecans (OCD) lesions of the knee on a child’s health-related quality of life has not previously been quantified. Preference-based health utility assessment allows patients to assign quality-of-life valuations (utilities) to different health states and conditions. Purpose: To determine (1) patient-reported utility scores for health states associated with pediatric OCD lesions of the knee and (2) whether these scores are associated with patient demographics or disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…17,30,31 This is in contrast to the common belief of hip arthroscopy being for the young and active population and several studies indicate poorer outcomes of hip arthroscopy for the middle age and older population. 32,33 The ratio of women undergoing arthroscopic surgery is in our study very similar to the population in the United Kingdom and in the state of New York with a combined range of 55-60% but distinctly different from the Swedish cohort where two-thirds are males. The difference could be due to the relatively smaller numbers in the Swedish study (n=606) or related to a cultural difference between surgeons in different countries.…”
Section: Discussionsupporting
confidence: 58%
“…17,30,31 This is in contrast to the common belief of hip arthroscopy being for the young and active population and several studies indicate poorer outcomes of hip arthroscopy for the middle age and older population. 32,33 The ratio of women undergoing arthroscopic surgery is in our study very similar to the population in the United Kingdom and in the state of New York with a combined range of 55-60% but distinctly different from the Swedish cohort where two-thirds are males. The difference could be due to the relatively smaller numbers in the Swedish study (n=606) or related to a cultural difference between surgeons in different countries.…”
Section: Discussionsupporting
confidence: 58%
“…24 Osteochondritis dissecans (OCD) is a known pathology resulting in symptomatic osteochondral lesions in pediatric and adolescent knees with risk of future arthrosis when left untreated. 1 , 2 , 25 , 43 , 44 While activity modification, off-loading the lesion, surgical stimulation for healing, and stabilization of unstable lesions are treatment options to salvage the pathologic lesion, the treatment of unsalvageable defects presents a challenging problem, particularly in the young knee.…”
mentioning
confidence: 99%
“…Previous studies have indicated that common pediatric orthopaedic knee injuries can be associated with exceedingly low utility values, showing just how debilitating such problems might be. Adjei et al 1 described utility scores as low as 0.15 in pediatric patients with osteochondritis dissecans lesions of the knee. In another study, adolescent patients with recurrent patellofemoral dislocations after treatment reported median utility scores of 0.20.…”
Section: Methodsmentioning
confidence: 99%
“…19 This surgery restores joint kinematics 12,27 and improves patient quality of life, 4,27 but patient satisfaction after surgery, especially in younger patients, is strongly linked to the patient's ability to return to playing sports. 24 The shortto midterm financial burden after ACLR and subsequent return to play (RTP) is dominated by 2 major costs: (1) the cost of revision surgery in the approximately 8% of patients who suffer graft failure and (2) the cost of ACLR for contralateral ACL rupture in the approximately 12% of patients who experience contralateral ACL injury. 16,21 Recent research has shown that programs aimed at primary prevention of ACL rupture can be effective, 29 reducing ACL rupture risk by up to 50%.…”
mentioning
confidence: 99%